147k views
1 vote
Ughhhhhhhhh last one

Ughhhhhhhhh last one-example-1
User TheRusskiy
by
5.2k points

1 Answer

4 votes

Answer:

c) x=13

Explanation:

4x + 2 = 90 − 36

Step 1: Simplify both sides of the equation.

4x + 2 = 90 − 36

4x + 2 = 90 + −36

4x + 2 = (90 + −36) (Combine Like Terms)

4x + 2 = 54

4x + 2 = 54

Step 2: Subtract 2 from both sides.

4x + 2 − 2 = 54 − 2

4x = 52

Step 3: Divide both sides by 4.

4x/ 4 = 52/ 4

x=13

if you need a shorter way to get this... is to do what i did and just used MathPapa's algebra calculator and put in "4x + 2 = 90 - 36" cause that's basically what the question is asking you to use... im not saying to do my method... im just saying that's how i got it

Ω Entity001 And Project Omega Ω

User Baskara
by
5.0k points